Perancangan sistem informasi pengarsipan berbasis website - Dedek Lulus Kurniawan; Ito Riris Immasari; Anton Zulkarnain Sianipar (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The rapid development of technology causes an increase in the need for information. The problems encountered in the system that has been running as it is today. The correspondence archiving system at the Leadership Administration Bureau still uses the manual method, so that the processing and data retrieval process becomes long and less efficient. The results of the analysis of the system that will be designed in accordance with the formulation of existing problems and discuss the results of observations with employees at the Leadership Administration Bureau that use this filing application flexibly in completing their tasks. Such as importing incoming letters, looking for letters, and borrowing letters easily, quickly, and efficiently. Therefore, this archiving information system is made in order to help agencies or companies to increase effectiveness in processing archive data by minimizing the possibilities of errors that will occur and so that information security can be guaranteed.